Competition Analysis of Regional Language and English In The Globalization Era - Vika Fransisca; Nur Alifah; Irma Nuraeni Salsabila (Syntax Corporation, 2022)
Language is the main communication tool. Apart from being a means of communication, language also has a role as a community wealth that needs to be preserved, this role is the role of regional languages. The role of the English as a foreign language is as tool of communicating between people in the world. This study aims to increase knowledge about the competition of regional languages ​​and English in the era of globalization. Data collection was carried out using a literature review method and a qualitative approach. The results of the analysis show that the use of regional languages ​​has been shifted by English in this globalization era. This happens not only in urban communities but also in rural communities.